Sovereign debt in the Americas: New data and stylized facts - Kevin Cowan; Eduardo Levy-Yeyati; Ugo Panizza; Federico Sturzenegger (Inter-American Development Bank, Research Department, 2006)
The paper presents a new database on sovereign debt in the Americas, describing the sources used and briefly discussing several methodological issues. The paper also highlights major trends in level and composition of public debt in the Americas, discussing debt dollarization in detail.
Keywords: 330; Öffentliche Schulden; Statistische Datenbank; Amerika